Model Bisnis Triple Bottom Line Pasar Komunitas Makanan Sehat dan Pengembangannya dalam Mewujudkan Rantai Pasok Pangan Berkelanjutan - Kristia Kristia (University of Merdeka Malang, 2019)
The purpose of this study is to map explicitly about the triple bottom line business model that has been practiced by three healthy food community markets in Yogyakarta, namely Pasar Kamisan, Pasar Moncer, and Pasar Mustokoweni. The research method uses a qualitative method, especially with a multi-sites approach, where data obtained from the process of observation and in-depth interviews with stakeholders. Data analysis uses combination of business model canvas approach and SPOT matrix analysis. The study reveals that the community market needs to innovate performance on the nine blocks of their triple bottom line business model in terms of improving the quality of organizational performance and playing an optimal role in realizing a sustainable food supply chain.https://doi.org/10.26905/jmdk.v7i2.3301